2016
DOI: 10.1373/clinchem.2015.250514
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Clinical Decision Support Rules to Reduce Repeat Measurement of Serum Ionized Calcium, Serum Magnesium, and N-Terminal Pro-B-Type Natriuretic Peptide in Intensive Care Unit Inpatients

Abstract: BACKGROUND:We assessed the impact of clinical decision support (CDS) rules within the electronic health record for ionized calcium (iCa), serum magnesium (Mg), and N-terminal pro-B-type natriuretic peptide (NT-proBNP) in intensive care unit (ICU) inpatients at a large academic center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 20 publications
(15 reference statements)
1
8
0
1
Order By: Relevance
“…In contrast, changing CK-MB to a research-only test and creating a hard stop for FTP virtually eliminated orders. These findings corroborate previous studies that have shown significant test volume reduction with hard stop interventions45–47 and less impact with soft stops 43 46 48–50. This could be attributable to alert fatigue51 since the per cent reductions following soft stops tend to be similar regardless of test type which suggests an underlying systematic process.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, changing CK-MB to a research-only test and creating a hard stop for FTP virtually eliminated orders. These findings corroborate previous studies that have shown significant test volume reduction with hard stop interventions45–47 and less impact with soft stops 43 46 48–50. This could be attributable to alert fatigue51 since the per cent reductions following soft stops tend to be similar regardless of test type which suggests an underlying systematic process.…”
Section: Discussionsupporting
confidence: 90%
“…Dans notre étude, la diminution significative d'examens tels que les bilans lipidiques (-80 %), les mesure d'HbA1C (-93 %), les groupages sanguins (-62 %) et RAI (-18 %) reflète largement la redondance fréquente de ces examens dans la pratique quotidienne et le fait qu'elle semble pouvoir être évitée par des moyens simples (via le patient ou son laboratoire habituel). Des alertes informatiques peuvent également permettre d'identifier et limiter la multiplication d'examens non justifiées [11], mais la consultation des données antérieures n'est souvent applicable que pour un centre donné, à moins de mettre en réseau des résultats biologiques de plusieurs centres hospitaliers.…”
Section: Figure 3 : éVolution Des Volumes De Prescription Des Examensunclassified
“…Prior studies have addressed the use of CDSS on laboratory ordering practices in the outpatient setting, but few have addressed the utility in the inpatient setting with only a recent emphasis on targeting redundant laboratory ordering . We conducted a prospective pilot study to evaluate the effect of nonintrusive CDSS on the inpatient utilization of serum and red blood cell (RBC) folate levels, hepatitis C virus (HCV) viral loads (VL) and genotypes, and type and screens (T&S) in a large academic centre.…”
Section: Introductionmentioning
confidence: 99%